Sensory neuron-derived eph regulates glomerular arbors and modulatory function of a central serotonergic neuron. - Singh, A.P.; Das, R.N.; Rao, G.; Aggarwal, A.; Diegelmann, S.; Evers, J.F.; Karandikar, H.; Landgraf, M.; Rodrigues, V.; Vijayraghavan, K. (PLoS Genetics, 2013)
Olfactory sensory neurons connect to the antennal lobe of the fly to create the primary units for processing odor cues, the glomeruli. Unique amongst antennal-lobe neurons is an identified wide-field serotonergic neuron, the contralaterally-projecting, serotonin-immunoreactive deutocerebral neuron (CSDn). The CSDn spreads its termini all over the contralateral antennal lobe, suggesting a diffuse neuromodulatory role. A closer examination, however, reveals a restricted pattern of the CSDn arborization in some glomeruli. We show that sensory neuron-derived Eph interacts with Ephrin in the CSDn, to regulate these arborizations. Behavioural analysis of animals with altered Eph-ephrin signaling and with consequent arborization defects suggests that neuromodulation requires local glomerular-specific patterning of the CSDn termini. Our results show the importance of developmental regulation of terminal arborization of even the diffuse modulatory neurons to allow them to route sensory-inputs according to the behavioural contexts.